La poesia italiana del Novecento e la funzione d’Annunzio: ipotesi di lavoro - Verdone, Alessio (Archivio d’Annunzio, 2021)
Gabriele d’Annunzio was frequently excluded from the generative matrix of the Italian poetical twentieth century. It is time to restore the truth free of any ideological biases. In order to do that, it is necessary to retrace the studies conducted by d’Annunzio’s successors who tried to explore different ways to reckon with his work. Studies of that kind would make it possible to hypothesise a methodology to use for a systematic investigation aimed at revealing the entity of the qualitative and quantitative impact d’Annunzio’s work has had on much of the Italian poetry. It would subsequently be possible to draft a rough analytic route to use as starting point for more substantial future investigations.